The Interplay of Fiqh, Adat, and State Marriage Law: Shaping Legal Consciousness of Sasak Women - Jumarim; Ilyya Muhsin; Muhammad Chairul Huda (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2024)
Sasak women grapple with a legal conundrum stemming from the coexistence of multiple marriage legal frameworks encompassing fiqh, adat, and state law. This intricate legal pluralism dynamically shapes the legal consciousness of Sasak women as they navigate the selection of legal avenues to secure legality and address their marital legal challenges. This study pursues two primary objectives: firstly, to examine the intricate interplay among fiqh, adat, and state marriage law concerning the provision of legal certainty and protection for Sasak women; secondly, to probe into the manifestations of legal consciousness arising from the plural marriage legal frameworks. Data were collected through document analysis, literature review, and in-depth interviews with selected Sasak women. The findings illuminate a dynamic interplay among fiqh, adat, and state marriage law across various marital facets, including prenuptial considerations, minimum marriage age, marriage prerequisites and pillars, marriage contracts, residency, polygamy, divorce, and reconciliation. Moreover, the study identifies three distinct forms of legal consciousness emerging among Sasak women: ‘before the law’ when confronting fiqh, ‘with the law’ when embracing formal legal mechanisms to address marital issues, and ‘against the law’ when eschewing formal legal provisions. In conclusion, state marriage laws are more progressive in providing legal certainty and protection for women but lacking criminal sanctions/fines weakens their position compared to religious law (fiqh) and customs (adat). Ultimately, this shapes the legal consciousness of Sasak women in diverse ways.